FLORA OF UZBEKISTAN - Zulaykho (EPRA International Journal of Research and Development (IJRD), 2024)
The flora and fauna of Uzbekistan is so diverse that it seems incredible how these representatives of flora and fauna can get along on the same territory. Here you can see such contrasts: snow-capped mountain peaks, green valleys and harsh steppes. Such a variety of landscape is explained by the interesting location of Uzbekistan. Most of the total territory of the state is occupied by the steppe, where wormwood, saxaul, tamarisk, and sandy acacia grow. In spring, when the steppe comes to life and blooms, it is very beautiful here, but, unfortunately, this period is quite short.